Restructuring the financial structure - Jerome Levy Economics Institute of Bard College (Levy Economics Institute of Bard College, 1992)
Table of Contents: Preface, by Dimitri B. Papadimitriou; Introduction, by Hyman P. Minsky; Personal Views on Financial Reform, by Anthony M. Solomon; Fundamental Change Little by Little: Banking Evolution, by Alex J. Pollock. Abstract: To avoid excessive concentration of economic and financial power, Athony M. Solomon recommends institutional and regulatory reform of the financial system by such means as nationwide banking, restrictions on federal deposit insurance, consolidation of financial regulation, balancing numerical standards with supervisory discretion, increased accountability of banks' management boards, and leveling the playing field across institutions, markets, and countries. Alex J. Pollock notes that technological advances, demographic changes, and other dynamics have not been adequately absorbed in the theoretical or practical functions of financial institutions. He recommends narrow banking as the framework for the optimal banking system.
Keywords: 330